SMART INDOOR VERTICAL FARMING MONITORING USING IoT - Bhuvaneswari, P.; M.G., Priyanka; S, Sandeep; R, Sridhar; R, Swaroop (The journal of contemporary issues in business and government, 2021)
The population of the world is expected to reach around 9.7 billion by the end of the year 2050. Currently, around 56% of the world‟s population lives in the urban areas, putting a lot of pressure on the maintenance of the air quality and the greenery in these areas. But the issue is that there is lack of space for cultivation in urban areas where urban gardening comes into picture. Human labour is involved in traditional methods of monitoring and farming and is it is time consuming. Vertical farming is the practice of growing plants in the vertically inclined surfaces or in vertically stacked layers. Here, plants are grown in a controlled environment. The proposed system uses the concepts of artificial photosynthesis, vertical and zone-wise crops production and the Internet of Things. This increases the productivity. By using the various sensor networks, the environmental parameters can be noted. The retrieved data is stored and displayed on a customized webpage which can be accessed through mobile app. Thus, the indoor vertical farm can be monitored and controlled even without direct presence of the cultivator at the plant environment. The variations in the individual sensor‟s data with respect to time can be graphically plotted for the improved analysis and monitoring of the system. Increasing population demands increase in food production by the next decade. Internet of things is implemented in vertical and indoor farming to establish a smart way of cultivation. Basic functions like monitoring the soil moisture, temperature, humidity are performed. Artificial photosynthesis for the plants using grow-lamps and drip irrigation is implemented to maintain the urban gardens. Using GSM technology systematic alerts regarding the status of garden to the user at regular intervals of time is delivered. An android app interface is also implemented in the proposed system to remotely control the garden functioning hence enhancing the smart way of agriculture.